KEBIJAKAN PEMERINTAH TERHADAP PENERAPAN APLIKASI AGRIBISNIS STORE DI DESA PATTONDON SALU - Anita S; Abdul Jabbar; Akhyaruddin Hakim; Bahtiar Herman; Kamal Kamal (FISIP Universitas Muhammadiyah Sidenreng Rappang, 2022)
The purpose of this research, to find out Governent Policy on the application of Agribusiness Store in the Village of Pattondon Salu, Maiewa District, Enrekang Regency, the data analysis technique used is descriptive statistics using data collection technique including questionnaire, interview, and observation. The population in this study were 2.380 people and the sampling used was probability sampling with a random sampling technique in order to obtain a sample of 88 people. Data analysis was performed with the help of the SPSS 21 program. The results of this study indicate that the planning of government policies on the application of agribusiness store aplications, in the Village of Pattondon Salu, Maiwa District, Enrekang regency, is at a percentage of value t count ≥ t table (5,024> 1,6627) with Y = 4,676 + 0,277 X or is the good category, while the aplications of agribusiness store applications is at a percentage of 86 % with an ideal 86,33% from 100% which is expected or is in the good category. Each indicator is in the good category with the percenatage of the producer role indicator at 88%, and the media role indicator at 86%.